Dissolved iron speciation results from 2019 Bermuda Atlantic Iron Time-series (BAIT) cruises EN631, AE1909, AE1921, AE1930 in the Western Subtropical North Atlantic Gyre from March to November 2019 (BAIT Project) - Kristen Buck; Salvatore Caprara (Biological and Chemical Oceanography Data Management Office (BCO-DMO), 2022)
Dissolved iron speciation results from 2019 Bermuda Atlantic Iron Time-series (BAIT) cruises